Misunderstandings and ambiguities in strategic purchasing in low‐ and middle‐income countries. (16th July 2020) - Paul, Elisabeth; Brown, Garrett W.; Ridde, Valéry
Summary: Strategic purchasing is branded as an approach that is necessary for progress towards universal health coverage. While we agree that publicly purchased health services should respond to society's needs and patient expectations, and thus generally endorse strategic purchasing, here we would like to explore two emerging concerns within current discussions in low‐ and middle‐income countries. First, there exists a great deal of misunderstanding and conceptual unclarity, within practitioner groups, around the concept of strategic purchasing and what instruments it incorporates. Second, there is a growing trend to regularly fuse strategic purchasing into a performance‐based financing (PBF) discourse in ways that increasingly blur their distinctive properties and policy orientations, while perhaps too easily obfuscating potential tensions. We believe the discourse on strategic purchasing would benefit from better conceptual clarity by dissociating and prioritising its two objectives, namely: priority should be given to needs‐based allocation of resources, while rewarding performance is a subsequent concern. We argue there is a need for a more thoroughgoing conceptual and empirical re‐examination of strategic purchasing's priorities, its link with PBF, as well as for a wider evidence‐base on what strategic purchasing tools exist and which are most appropriate for diverse contexts.